Identification of Putative Molecular Markers Associated with Root Traits in Coffea canephora Pierre ex Froehner. (3rd March 2015) - Achar, Devaraja; Awati, Mallikarjuana G.; Udayakumar, M.; Prasad, T. G.
Abstract : Coffea canephora exhibit poor root system and are very sensitive to drought stress that affects growth and production. Deeper root system has been largely empirical as better avoidance to soil water limitation in drought condition. The present study aimed to identify molecular markers linked to high root types in Coffea canephora using molecular markers. Contrasting parents, L1 valley with low root and S.3334 with high root type, were crossed, and 134 F1 individuals were phenotyped for root and associated physiological traits (29 traits) and genotyped with 41 of the 320 RAPD and 9 of the 55 SSR polymorphic primers. Single marker analysis was deployed for detecting the association of markers linked to root associated traits by SAS software. There were 13 putative RAPD markers associated with root traits such as root length, secondary roots, root dry weight, and root to shoot ratio, in which root length associated marker OPS1850 showed high phenotypic variance of 6.86%. Two microsatellite markers linked to root length (CPCM13400 ) and root to shoot ratio (CM211300 ). Besides, 25 markers were associated with more than one trait and few of the markers were associated with positively related physiological traits and can be used in marker assisted trait selection.